1991
DOI: 10.1063/1.460817
|View full text |Cite
|
Sign up to set email alerts
|

The time dependent solution of the Smoluchowski equation: Kinetics of escaping from the well for different dimensionalities

Abstract: A recently developed method of analytical solution of the Smoluchowski equation is applied to the investigation of the kinetics of diffusional escape from a potential well for different space dimensionalities n. The kinetics is described by the time dependence of the well occupation probability Nn(t). The formulas derived are valid for times longer than the time t0=a 2/D of relaxation within the well U(r) [a is the Onsager’s radius determined by U(a)=kT ]. In the absence of absorption (or reaction) within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 11 publications
1
81
0
Order By: Relevance
“…As shown by Shushin [17], the decay kinetics of diffusional escape from such a potential well exhibits two regimes: (i) an exponential decay on a short time scale (with rate constant W=W r +W d , where W r,d are the recombination and dissociation rates of the radicals in the potential well, respectively), and t -1/2 behavior on the longer time scale, due to slow recombination of radicals that escaped beyond the Onsager radius a, at which U(a)=-kT. In this theory, the escape probability p d of the radical partners is equal to W r /W and the effective radius R eff of the reaction in the bulk is given by a product a(1-p d ) [18]. Fig.…”
Section: Kinetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…As shown by Shushin [17], the decay kinetics of diffusional escape from such a potential well exhibits two regimes: (i) an exponential decay on a short time scale (with rate constant W=W r +W d , where W r,d are the recombination and dissociation rates of the radicals in the potential well, respectively), and t -1/2 behavior on the longer time scale, due to slow recombination of radicals that escaped beyond the Onsager radius a, at which U(a)=-kT. In this theory, the escape probability p d of the radical partners is equal to W r /W and the effective radius R eff of the reaction in the bulk is given by a product a(1-p d ) [18]. Fig.…”
Section: Kinetic Analysismentioning
confidence: 99%
“…Fig. 1 demonstrates the fit of the experimental kinetics to Shushin's theory expressions [17,18] for the survival probability of a radical pair migrating out of the potential well.…”
Section: Kinetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Shushin [56][57][58] has considered kinetics of the diffusion dissociation of interacting molecules for the general shape of the interaction potential possessing a well and a barrier at small distances. It has been shown that the kinetics of the diffusion escape from a well is exponential at short times and follows a power law at long times [56][57][58].…”
Section: Conductivity Kinetics Of Geminate Radical Ion Pairsmentioning
confidence: 99%
“…The well is assumed to be isotropic and highly localized (short range). Though, detailed analysis shows 16,17 that fairly deep potential well resulted, for example, from the Coulomb interaction (at large r) can also be considered as highly localized in some conditions.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%